AN ACOUSTIC ANALYSIS OF VOICELESS ALVEOLAR PLOSIVE /t/ IN SUNDANESE, INDONESIAN, AND ENGLISH BY SUNDANESE SPEAKERS - Jeri Sukmawijaya; Sutiono Mahdi; Susi Yuliawati (Metahumaniora, 2020)
A voiceless alveolar plosive /t/ is pronounced with many variations. In English, it is perceived to have an aspiration when it is in the initial segment of a word in a stressed syllable while Sundanese and Indonesian do not aspirate it. The study focuses on finding out Voice Onset Time (VOT) or duration of /t/ in Sundanese, Indonesian, and English produced by Sundanese speakers. The method used is quantitative and qualitative (mix method). The data are obtained from the voice recording of eighteen undergraduate students. They are all native Sundanese speakers who are learning English at IKIP Siliwangi Cimahi. The voice recordings are analyzed and measured by acoustic analysis by using PRAAT software. The result shows the average VOT or duration of /t/ in the initial segment of the word in Sundanese and Indonesian is identical, namely 20 ms. It indicates that they do not aspirate /t/ in Sundanese and Indonesian. Additionally, they transfer the way they produce /t/ in their two languages into English as their foreign language. It can be seen from the average VOT or duration of /t/ in the initial segment of the word in English that lasts 29 ms. This finding can be a reference to other researchers who want to know the necessary duration of /t/ in Sundanese and Indonesian produced by Sundanese speakers.